Breaking the Illusion of Disembeddedness in Science Fiction Movies Interstellar and The Martian - Dangaura, Mohan (Bon Voyage, 2019)
This paper critically examines two Hollywood science fictions movies Interstellar and The Martian from the notion of environmental crisis and human’s desperate effort to protect its serenity. Particularly, I am interested in exploring the issue of illusionistic anthropocentrism. I am interested in knowing why the feelings of superiority and self-sufficiency in human beings make them live with illusion of disembeddedness from nature. The major objective of this paper is to pinpoint the ecological crisis in future world and the invention of artificial habs or digital earth for survival through Hollywood films. The birth of the digital Earth ensures the doom of green earth and warns us to contemplate on our own earth instead lurking after space mission ignoring the nature’s exploitation. For this, I have used ecocritical perspective. Especially, I have drawn upon Lynn Townsend White Jr. and Val Plumwood’s notion of ecocriticsm and environmental crisis. This study is going to be important because it will answer the roots of our current ecological crisis and environmental pollution.